Systemic Lupus Erythematosus (SLE): A review on the prevalence, clinical manifestation, and disease assessment - Malarvili Selvaraja; Maha Abdullah; Anim Md Shah; Masita Arip; Syafinaz Amin Nordin (Progress in Microbes and Molecular Biology)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease with a varying clinical phenotype. This disease occurs when the body’s tissues are attacked by its own immune system. The aetiology of SLE is not fully understood, but both genetic predisposition and ecological triggers are thought to be involved in the disease manifestation. The study on the prevalence of SLE allows us to identify potential risk factors associated with the disease for the disease and allows proper management and treatment in response to overall disease burden. Hence, this review aims to discuss the prevalence, mortality, clinical manifestation and disease assessment of SLE.